Surgical Treatment of an Infected Nonunion of the Middle Third of the Femur Associated with Femoral Shortening in a Hemophilia Patient - Ahmet Salduz; Özcan Kaya; Halil İbrahim Balci; Turgut Akgul; Fatih Dikici; Bülent Zülfikar; Mehmet Kocaoğlu (Case Reports in Orthopedics)
The management of nonunion and limb length discrepancy has remained a constant challenge in hemophilic patients. In this study, we aimed to present the treatment of femur infected nonunion and limb length discrepancy in a twenty-seven-year-old patient with hemophilia type A. A 27-year-old male patient with hemophilia type A referred to our institution for the treatment of right femur infected nonunion and 10 cm shortness of the femur. Resection of the nonunion site and bone-to-bone fixation with autologous bone grafting were performed. Compression to the pseudoarthrosis site and distraction from new osteotomy site were applied with the unilateral external fixator. Union was achieved, and 6 cm lengthening was obtained according to the initial length. Patient was followed up for 7 years. After this treatment, the patient is able to walk with full weight bearing on the affected extremity with 4 cm shortening which is compensated by the heel lift. The results of this case indicate that limb lengthening and treatment of nonunion with the external fixation could be reliable and effective method for hemophilic patients.